Impact of layup rate on the quality of fiber steering/cut-restart in automated fiber placement processes - Chen Jihua; Chen-Keat Teresa; Hojjati Mehdi; Vallee AJ; Octeau Marc-Andre; Yousefpour Ali (Science and Engineering of Composite Materials, 2015)
Developing reliable processes is one of the key elements in producing high-quality composite components using an automated fiber placement (AFP) process. In this study, both simulation and experimental studies were carried out to investigate fiber steering and cut/restart under different processing parameters, such as layup rate and compaction pressure, during the AFP process. First, fiber paths were designed using curved fiber axes with different radii. Fiber placement trials were then conducted to investigate the quality of the steered fiber paths. Furthermore, a series of sinusoidal fiber paths were fiber placed and investigated. Moreover, a six-ply laminate with cut-outs in it was manufactured in the cut/restart trials. The accuracy of the fiber cut/restart was compared at different layup rates for both one- and bi-directional layups. Experimental results show that it was possible to layup steered fiber paths with small radii of curvature (minimum 114 mm) designed for this study when the proper process condition was used. It was observed from the cut/restart trials that the quality of tow cut was independent of layup speed; however, the accuracy of tow restart was related to the layup speed. The faster the layup speed, the less accurate was the tow restart.